Micro, Small and Medium Enterprises (MSMEs) Financing and Unemployment Rates in Nigeria - Enechukwu, Humphrey; Akintoye, Rufus; Ogboi, Charles (International Journal of Economics and Financial Issues, 2025)
Globally, a low unemployment rate is highly desirable and generally associated with favorable economic conditions and a growing economy. Incidentally, the unemployment rates in Nigeria are progressively on the increase. Studies have shown sufficient micro, small, and medium enterprise (MSME) financing has the capability of solving the problem of unemployment rates in Nigeria. Concidentally, the extent to which MSME financing has impacted unemployment rates in Nigeria has remained uncertain. Consequently, this study investigated the effect of MSME financing on unemployment rates in Nigeria. In addressing this concern, the study employed an ex post facto research design, using a time series of secondary data extracted from the Central Bank of Nigeria, Nigerian Statistics Bulleting, World Development Indicator, and World Income Inequality Database for a period of 32 years spanning from 1992 to 2023. The Vector Error Correction Model was adopted for the data analysis. The finding showed that MSME financing had a joint significant effect on unemployment rates in Nigeria. The study recommended that the government and policymakers should expedite economic policy to ensure sufficient financing of the MSMEs in Nigeria.